Risk and Protective Factors of Oppositional Defiant Disorder in Children with Stuttering: Unraveling Familial Dynamics - Goshayeshi, Mona; Samadieh, Hadi; Tanhaye Reshvanloo, Farhad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The current study aimed to explore the role of familial conflict, psychological distress, and problem-resolution techniques on the prevalence of Oppositional Defiant Disorder (ODD) in stuttering children. Methodology: This investigation employed a correlational research design. The sample comprised six-year-old children and their mothers from Mashhad. The study included 196 preschoolers (106 girls and 90 boys) selected through convenience sampling. The Oppositional Defiant Disorder Rating Scale (ODDRS), Family Environment Scale (FES), Family Distress Index (FDI), and Family Problem-Solving Communication (FPSC) were utilized for data collection. A linear regression analysis was performed with SPSS version 27 to assess the interrelations among the variables. Findings: The analysis identified family conflict (β=0.35), distress (β=0.39), and problem-solving strategies (β=-0.40) as significant predictors of ODD symptomatology. Notably, family conflict and distress were positively correlated with ODD symptoms, whereas problem-solving strategies were inversely related. These factors collectively accounted for 49% of the variance in ODD symptomatology. Conclusion: This research contributes to the existing literature by amalgamating various familial elements—conflict, distress, and problem-solving strategies—into an integrated framework to better comprehend the etiology of ODD in children.